Predictors of renal recovery in recipients of liver transplant alone who met 2017 simultaneous liver‐kidney transplant criteria. Issue 12 (5th October 2022) - Cui, Jiawei; Spann, Ashley; Shingina, Alexandra; Schaefer, Heidi; Slaughter, James C.; Matsuoka, Lea; Alexopoulos, Sophoclis; Izzy, Manhal
Abstract: Background: Severe renal dysfunction is common among liver transplant (LT) candidates and often prompts simultaneous liver‐kidney transplantation (SLKT) consideration. In view of 2017 United Network of Organ Sharing (UNOS) criteria for SLKT, we investigated the likelihood and predictors of renal recovery among patients who met the aforementioned criteria yet received liver transplant alone (LTA). Methods: We retrospectively analyzed relative renal recovery (RRR; increase in eGFR to >30 ml/min) in adult LTA recipients between 1/2009 and 1/2019. Results: Of 1165 LT recipients, 54 met 2017 UNOS criteria, with 37 receiving LTA. RRR occurred in 84% of LTA recipients, none of whom had pre‐LT eGFR <20 ml/min. Sustained RRR (>180 days) occurred in 43% of patients. While prolonged pre‐LT severe renal impairment (eGFR < 30 ml/min) predicted failure to have sustained RRR (HR .19 per 90‐day, CI .04–.87, p  < .005), having an eGFR measurement of >30 ml/min within 90 days pre‐LT (HR 5.52, CI 1.23–24.79, p .01) associated with achieving sustained RRR. Sustained RRR was protective against the composite outcome of renal replacement therapy, kidney transplant, and death (HR .21, p .01). Conclusion: LT candidates who meet 2017 UNOS criteria for SLKT yet undergo LTA can still have relative renal recovery post‐LT, exceeding 80% on short‐term follow‐up and 40% on long‐term follow‐up. eGFR trends within 90 days pre‐LT can predict sustained renal recovery, which appears protective of adverse outcomes. These recovery rates advocate for applying the more restrictive criteria for SLKT outlined in this article and increasing utilization of the safety net (SN) policy for those who do not meet the proposed criteria.